Argostemma tortilobum (Rubiaceae), a new species from Vietnam - Fang, Ke-Yi; Tong, Yi-Hua; Vu, Tien-Chin; Nguyen, Khang-Sinh; Xia, Nian-He (Phytotaxa, 2022)
Argostemma tortilobum, a new species endemic to Vietnam, is described and illustrated. The species is morphologically most similar to A. sarmentosum, but differs in having erect stem without runners, densely pilose peduncle and twisted corolla lobes with ciliate margins.